2017
DOI: 10.17925/ee.2017.13.02.51
|View full text |Cite
|
Sign up to set email alerts
|

Beta-cell Insufficiency

Abstract: Abstract‘Beta-cell failure’ is a frequently used term to describe the structural and functional inability of the cells to fulfil their metabolic responsibility. This editorial reviews the anatomy and physiology of the beta cell, and describes factors which regulate this. The authors focus on semantics, comparing the phrases ‘beta-cell failure’, ‘functional mass’, and ‘beta-cell insufficiency’. They suggest the use of ‘beta-cell insufficiency’, with descriptors such as ‘partial’ and ‘complete’, or ‘reversible’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Pancreatic beta cells are responsible for insulin synthesis and release, the main hormone in glucose homeostasis, by controlling absorption, digestion, conversion, and storage of carbohydrates [ 30 ]. Beta cell insufficiency is a general term mainly referred to as the structural or functional inability of the pancreatic beta cells to fulfill their metabolic activities and impair insulin release in response to meal [ 31 ]. It was confirmed that beta cell failure leads to chronic hyperglycemia, which characterizes type 2 DM [ 31 ].…”
Section: Pathophysiologic Links Between Physical Inactivity and Insulin Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…Pancreatic beta cells are responsible for insulin synthesis and release, the main hormone in glucose homeostasis, by controlling absorption, digestion, conversion, and storage of carbohydrates [ 30 ]. Beta cell insufficiency is a general term mainly referred to as the structural or functional inability of the pancreatic beta cells to fulfill their metabolic activities and impair insulin release in response to meal [ 31 ]. It was confirmed that beta cell failure leads to chronic hyperglycemia, which characterizes type 2 DM [ 31 ].…”
Section: Pathophysiologic Links Between Physical Inactivity and Insulin Resistancementioning
confidence: 99%
“…Beta cell insufficiency is a general term mainly referred to as the structural or functional inability of the pancreatic beta cells to fulfill their metabolic activities and impair insulin release in response to meal [ 31 ]. It was confirmed that beta cell failure leads to chronic hyperglycemia, which characterizes type 2 DM [ 31 ]. Also, inherited abnormalities in beta cell mass or function are important precursors for dysglycemia and type 2 DM [ 31 ].…”
Section: Pathophysiologic Links Between Physical Inactivity and Insulin Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The three-stage model which lists beta-cell sufficiency, partial/reversible insufficiency, and complete/irreversible insufficiency, also appears a rational way of describing disease progression in T2D. 16 Objective markers are needed, however, and fasting and stimulated serum C-peptide are useful markers for functioning of beta cells. This has minimal relevance in clinical practice, and is used primarily in research settings.…”
Section: The Characteristics Of Diabetes and Methods For Measuring Itmentioning
confidence: 99%
“…(19) The general term "beta cell insufficiency" primarily refers to the impairment of the structural or functional capacity of the pancreatic beta cells to carry out their metabolic functions, thereby hindering the release of insulin in response to meals. (20) It has been established that type 2 diabetes is characterized by chronic hyperglycemia, which results from beta cell dysfunction. Additionally, hereditary variations in the mass or function of beta cells are significant predisposing factors for type 2 diabetes and dysglycemia.…”
Section: Type 2 Diabetesmentioning
confidence: 99%